Effectiveness of Public Services in Making Job Seeker Cards - Prasodjo, Tunggul; Firman, Ahmad; Idris, Muhammad; Asri, Asri (Pinisi Business Administration Review, 2023)
The services provided by the government to the community continue to undergo renewal, both in terms of paradigm and service format in line with the policies issued from these agencies as well as in the increasing demands of the community and changes in the government that are satisfactory even the community is still positioned as a helpless party and is realized in the framework of services.  This research includes quantitative descriptive research using a percentage formula. The population was 124 people, while the selected sample was 62 people.  The results showed that the results of the data processing showed that the average openness dimension was 14.87  in the good category. The simplicity dimension is 10.68 which is in the excellent category.  The certainty dimension is 14.77 is in the good category.  Justice is 10.82 which is in the excellent category. Safety and comfort is 13.71 is in the good category. Responsive dimension is 17.20 is in the good category